The medullary pacemaker nucleus is unnecessary for electroreceptor tuning plasticity in Sternopygus - Ferrari, MB (J Neurosci, 1989)
Tuberous electroreceptors of the weakly electric fish Sternopygus macrurus are closely tuned to the frequency of electric organ discharge (EOD), which is determined by a medullary pacemaker nucleus (PMN). Previous studies have demonstrated that androgens lower the frequency of PMN discharge and concomitantly lower the best frequencies (BFs) of electroreceptors. In order to determine if the PMN serves as an internal reference for the hormone-mediated returning of electroreceptors, the PMN was lesioned and the change in mean BF was measured for dihydrotestosterone (DHT)-implanted or control animals. DHT-implanted fish showed the characteristic lowering of mean electroreceptor BF by approximately 25%, a significant change compared with controls (p less than 0.01, Mann-Whitney). This result indicates that the PMN is not necessary for the hormone-mediated shift of electroreceptor tuning. In a related study, the contribution of the PMN to the genesis of tuning in regenerating electroreceptors was examined by removing a patch of cheek skin from PMN-lesioned fish. Regenerating electroreceptors became sharply tuned to the previous EOD frequency by 6 weeks in the same fashion as regenerating receptors in intact fish. In addition, intact receptors from PMN-lesioned fish remained tuned for up to 160 d. Together, these results demonstrate that the pacemaker nucleus is unnecessary for the maintenance, development, or hormone- mediated shift of receptor tuning.